Modeling and Performance Analysis of 400 Kv Transmission Lines under Lightning Impulse and Switching Overvoltages Using MATLAB/ANSYS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
High-voltage transmission lines are critical assets for the reliable operation of modern power systems, enabling large-scale electricity transfer across long distances with minimal losses. However, these lines are highly susceptible to transient overvoltages generated by both external and internal sources. External overvoltages typically result from lightning strikes, producing steep-front impulses that can cause insulation flashovers, while internal overvoltages are mainly associated with switching operations, resulting in slow-front surges that may sustain stress on the insulation for longer durations. Both types of overvoltages represent significant challenges to insulation coordination, system reliability, and overall operational safety.This research presents a detailed modeling and simulation study of 400 kV overhead transmission lines subjected to such electrical stresses. Two widely recognized simulation tools, MATLAB/Simulink and ANSYS Maxwell, were employed to provide a comprehensive analysis. MATLAB/Simulink was used to model surge propagation along transmission lines and to analyze the transient response of the network under different fault and switching scenarios. Meanwhile, ANSYS was utilized to investigate electric field distribution around polymeric insulators and to calculate leakage currents under non-uniform contamination and fog conditions, which are often responsible for partial discharges and long-term insulation degradation.The simulation scenarios included:• Application of a standard 1.2/50 μs lightning impulse to evaluate peak stress levels.• Switching surges during energization and fault-clearing operations to investigate slow-front overvoltages.The results revealed that lightning impulses produced higher peak voltages but of shorter duration, whereas switching overvoltages produced longer-lasting but lower-amplitude stresses. Furthermore, leakage current analysis demonstrated a 30–40% increase in polluted and humid environments, highlighting the importance of environmental considerations in insulation coordination.Overall, the findings confirm that accurate hybrid modeling using MATLAB and ANSYS significantly enhances the prediction of overvoltage behavior, supports optimized surge arrester placement, and improves insulation design. The integration of time-domain and field-distribution simulations provides engineers with valuable insights into mitigation strategies, thereby reducing the probability of insulation failure and improving the overall stability and reliability of high-voltage transmission systems.